Different strategies to improve isochrone voyage optimization algorithm - Chen, Yuhan; Mao, Wengang; Zhang, Chi (2023)
Voyage optimization can be essential in ship routing for autonomous and intelligent operations. Various optimization algorithms were proposed to search for optimal ship routing with minimized fuel consumption and accurate arrival time. In this paper, the Isochrone method, which is well-known for its robustness and efficiency, is further improved by different strategies to inherit the original capability of computation efficiency, and overcome its incompetence of multi-objective optimization, reliable convergence for approaching destination, and feasibility for practical navigation. Especially an innovative way of searching at a late stage is proposed, as well as a flexible evaluation of cost functions according to different optimization objectives. The improved Isochrone method can fast optimize a shipping route with multi-objective purposes, such as accurate expected time of arrival and minimum fuel consumption. The effectiveness and efficiency of different improved Isochrone methods are verified by several North Atlantic voyages collected by a chemical tanker.